ß-Alanine and the hormonal response to exercise - Hoffman, J.; Ratamess, N. A.; Ross, R.; Kang, J.; Magrelli, J.; Neese, K.; Faigenbaum, A. D.; Wise, J. A. (International Journal of Sports Medicine, 2008)
The effect of 30 days of ß-alanine supplementation (4.8 g per day) on resistance exercise performance and endocrine changes was examined in eight experienced resistance-trained men. An acute resistance exercise protocol consisting of 6 sets of 12 repetitions of the squat exercise at 70 % of one-repetition maximum (1-RM) with 1.5 minutes of rest between sets was performed before and after each supplemental period. Blood draws occurred at baseline (BL), immediate (IP), 15-minutes (15P) and 30-minutes (30P) postexercise for growth hormone, testosterone and cortisol concentrations. A 22 % (p < 0.05) difference in total number of repetitions performed at the end of 4 weeks of supplementation was seen between ß-alanine (BA) and placebo (PL), and ? mean power was greater in BA (98.4 ± 43.8 w) vs. PL (7.2 ± 29.6 w). Growth hormone concentrations were elevated from BL at IP and 15P for both groups, while cortisol concentrations were greater than BL at all time points for both BA and PL. No group differences were noted. No change from BL was seen in testosterone concentrations for either group. Results indicate that four weeks of ß-alanine supplementation can significantly improve muscular endurance during resistance training in experienced resistance-trained athletes. However, these performance gains did not affect the acute endocrine response to the exercise stimulus.